Économies d’échelle dans les opérations des caisses populaires du district de Québec - Khoury, Nabil (L'Actualité économique, 1977)
AbstractThe application of the computer to the servicing of deposit accounts at banks and non-bank financial intermediaries is a fairly recent development. Most empirical studies of economies of scale in this industry date prior to this technological transition. There is one notable exception, however, and that is the study by D. L. Daniel, W. A. Longbrake and N. B. Murphy (1972), in which they reported economies of scale in the servicing of checking deposits for computerized banks, especially when the number of such accounts exceeds the 10,600 mark. The present study examines the issue for a different type of computer-using deposit institution, namely: a sample of 128 Canadian Credit Unions located in the district of Quebec and referred to as the "Caisses Populaires" (C.P.'s). These institutions were chosen for the study because they present some unique characteristics and also because they were among the first Canadian financial institutions to computerize the servicing of their deposit operations.Following G. J. Benston (1970) and F. Bell and N. Murphy (1968), the data has been tested using two different models. The empirical results of both tests indicate that computerization did not generate any economies of scale in the checking deposit accounts. Further analysis reveals that the potential economies of scale were captured by the lessor of the equipment through a financial arrangement tying the rent to the number of cheking accounts to be serviced.